High entropy steel processed through mechanical alloying and spark plasma sintering: Alloying behaviour, thermal stability and mechanical properties - Jain H.; Shadangi Y.; Chakravarty D.; Dubey A.K.; Mukhopadhyay N.K. (My University, 2025)
In present investigation, a non-equiatomic high entropy steel (HES) was synthesized by mechanical alloying (MA) followed by spark plasma sintering (SPS). The Fe40Mn14Ni10Ti10Al15Si10–C1 HES milled up to 30 h was found to have a metastable dual-phase containing a major BCC (a = 2.872 Å; cI2) and a γ-brass type (a = 8.890 Å; cI52) phase having nanostructured grains of ∼10 ± 2 nm. The differential scanning calorimetry (DSC) thermogram exhibited the four exothermic heating events at 530 °C, 690 °C, 860 °C and 1000 °C. The phase transformation corresponding to the heating events was correlated with the ex-situ XRD of the as-milled powder. The phases evolved were Fe–Si solid solution, FCC, Fe5Si3 type and TiC phases. Fe40Mn14Ni10Ti10Al15Si10–C1 milled HES powder was consolidated through SPS at 900 °C and at 50 MPa. The SPSed HES were found to have a dual-phase structure containing a major FCC phase (a = 3.602 Å; cF4) and a minor BCC phase (a = 2.876 Å; cI2) along with the intermetallic phases like Fe5Si3 type (a = b = 6.808 Å, c = 4.745 Å; hP16) and TiC (a = 4.301 Å; cF8). The mechanical properties of these SPSed samples were discerned through instrumented microhardness and compression tests. The microhardness, elastic modulus, ultimate compressive strength and strain were found to be ∼10.4 GPa, ∼209 GPa, ∼2305 MPa and ∼15% respectively. This SPSed HES showed an excellent room temperature microhardness and strength which can be attributed to the co-existence of FCC phase along with the minor phases and hard intermetallics. The strengthening mechanism suggested that the grain boundary, dislocation, and precipitates strengthening were dominant. Attempts have been made to understand the phase evolution and the consequent mechanical properties in these HES. © 2022 Elsevier B.V.